Rewilding with the beaver in the Iberian Peninsula - Economic potential for river restoration - Veríssimo, D.; Roseta-Palma, C. (Nature-Based Solutions, 2023)
Nature restoration is essential to tackle the loss of biodiversity and to adapt and mitigate the effects of climate change. Recently the United Nations declared 2021 - 2030 the decade for the Restoration of Ecosystems, while the European Union 2030 Biodiversity Strategy includes restoration as a core pillar. Rivers and streams are a key component of ecosystems, yet many are in poor ecological condition. The Por- tuguese Environmental Agency (APA) ran a program from 2018 to 2020 to restore degraded watercourses through bioengineering interventions. Yet these do not restore missing ecological processes, while additional funding would be required to expand their range. Thus long-term improvement is not assured. Beavers used to inhabit the Iberian Peninsula and they have already been brought back to other areas, as a means to restore freshwater ecosystems. Beavers are ecosystem engineers, building dams, digging canals and cutting shrubs and trees. As a keystone species, beavers allow many others to thrive, delivering significant environmental and economic benefits. In this work we select, among the actions listed in the APA river restoration guide, those that beavers might perform. We value these actions in monetary terms as avoided costs, taking into consideration price intervals and expected beaver colony activity. We conclude that beavers have the potential to replicate many commonly-used river restoration actions, possibly saving millions of euros in interventions. Bringing back the beaver therefore seems a worthwhile endeavour, not only in Portugal but in the main river basins of the Iberian Peninsula. Furthermore, beavers could provide a boost to wildlife, increase landscape resilience to climate change and bring hope in the face of envi- ronmental challenges.